2016
DOI: 10.1159/000445369
|View full text |Cite
|
Sign up to set email alerts
|

Personality Profiles, Values and Empathy: Differences between Lacto-Ovo-Vegetarians and Vegans

Abstract: Background: Vegetarian nutrition is gaining increasing public attention worldwide. While some studies have examined differences in motivations and personality traits between vegetarians and omnivores, only few studies have considered differences in motivations and personality traits between the 2 largest vegetarian subgroups: lacto-ovo-vegetarians and vegans. Objectives: To examine differences between lacto-ovo-vegetarians and vegans in the distribution patterns of motives, values, empathy, and personality pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 48 publications
3
57
2
2
Order By: Relevance
“…In contrast to our finding in Study 1, in which vegetarians had lower scores in conscientiousness than meat eaters, prior studies have consistently reported that conscientiousness is negatively related to meat consumption (Keller & Siegrist, 2015;Kessler et al, 2016). It should be noted, however, that the present studies compared self-reported and selfidentified vegetarians and meat eaters, and did not assess actual meat consumption.…”
Section: Individual Differences Between Vegetarians and Meat Eaterscontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our finding in Study 1, in which vegetarians had lower scores in conscientiousness than meat eaters, prior studies have consistently reported that conscientiousness is negatively related to meat consumption (Keller & Siegrist, 2015;Kessler et al, 2016). It should be noted, however, that the present studies compared self-reported and selfidentified vegetarians and meat eaters, and did not assess actual meat consumption.…”
Section: Individual Differences Between Vegetarians and Meat Eaterscontrasting
confidence: 99%
“…In a study of older adults in Scotland, Mõttus et al (2013) further reported that openness, conscientiousness, and agreeableness were positively associated with a health-aware diet that included less meat consumption. Kessler et al (2016) investigated personality traits in an online survey of members and supporters of the German Vegetarian Society. In this study, vegetarians showed significantly less extraversion, along with higher openness, agreeableness, and conscientiousness compared to meat eaters; in addition, vegans reported significantly less neuroticism and extraversion, as well as higher openness, agreeableness, and conscientiousness compared to meat eaters (Kessler et al, 2016).…”
Section: Individual Differences Between Vegetarians and Meat Eatersmentioning
confidence: 99%
See 1 more Smart Citation
“…While motivations of vegetarians living in Western countries are mainly individual compositions of health, economic, environmental, social, ethical, and spiritual factors, vegetarians in India relate their dietary habits mainly to religious beliefs and traditional values [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Dr. Ram Manohar, einer der führenden Forscher aus der indischen Ayurvedamedizin und aus dem Land mit den mit Abstand meisten Vegetariern (40%) kommend, liefert eine Synthese über Bedeutung und medizinischen Nutzen vegetarischer Ernährungsweise aus Sicht der traditionellen indischen Medizin [12]. Dr. Christian Kessler, Dr. Holger Cramer und Kollegen berichten über die Ergebnisse einer Online-Umfrage bezüglich Werten und Persönlichkeitsaspekten von Vegetariern [13]. Dr. Markus Keller und Stine Müller schreiben schließlich über das Thema, das nach wie vor ein großer und vielleicht auch der letzte Gegenstand ist, der immer noch zu starken Kontroversen und Widerständen in der Medizin führt - vegane Ernährung in Kindheit und Schwangerschaft [14].…”
unclassified